A Postmodern Understanding of Toni Morrison’s Sula - Ekawati, Rosyida (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2014)
Postmodern fiction has unique features that distinguish its works from other works of fiction. It often blurs literary genres and breaks conventional narration. Toni Morrison’s novel titled *Sula*, a work that has triggered some critical work, is considered as one of the prime texts of this fiction. This article is a report on an investigation of the postmodern features of Morrison’s *Sula*. It is a descriptive qualitative study using the narration and conversation among the characters. It showed that the novel starts with paradox and ambiguity in the beginning. The author is able to judge the ethical or moral ramifications and decipher Sula as either an evil or a good person. It also criticizes patriarchal institution, gender displacement, and associative ambiguity.